(untitled) (Research, Society and Development, 2022)
The qualification of teaching, especially the teaching of Natural Sciences, it has been, in recent decades, the focus of debates and academic productions. It is presented as a consensus that teaching science in a contextualized way and that dialogue with the reality of students, it seems to be a path that may produce meaningful learning. The integration between the knowledge of the curricular components that make up the Natural Sciences favors this contextualization and may be a way of bringing new proposals to qualify teaching. It is interesting, therefore, to know how much research in the teaching of Natural Sciences is concerned with the theme of interdisciplinary teaching. Thus, the present article aims to assess how academic productions related to interdisciplinarity and shared teaching between the curricular components of the area of Natural Sciences are in the final years of Elementary School and High School in the period from 2017 to 202l. This is a bibliographic study that performs a literature review in CAPES Theses and Dissertations Bank, in the LUME Digital Repository of the Federal University of Rio Grande do Sul (UFRGS) and in Google Scholar, using specific descriptors. After the search, 9 scientific productions were found on shared teaching and interdisciplinarity in science teaching. The results showed that there are few academic productions related to the investigated theme, indicating that there is a need for greater attention in relation to the teaching of Natural Sciences in a more contextualized and integrated, in order to qualify learning in Basic Education.